Studies on Nondefective Adenovirus-Simian Virus 40 Hybrid Viruses I. A Newly Characterized Simian Virus 40 Antigen Induced by the Ad2(+)ND(1) Virus - Lewis, Andrew M. (1971)
The nondefective adenovirus 2 (Ad2)-simian virus 40 (SV40) hybrid virus, Ad2(+)ND(1), does not induce heat-labile SV40 T antigen but does induce a previously uncharacterized heat-stable SV40 antigen—the SV40 “U” antigen. This antigen is detectable by both immunofluorescence and complement fixation by using sera from hamsters with SV40 tumors. Sera from hamsters bearing SV40 tumors can be divided into two groups, those that react with both SV40 T and U antigens (T(+)U(+) sera) and those that react with SV40 T antigen only (T(+)U(−) sera). SV40 U-specific sera from monkeys immunized with Ad2(+)ND(1)-infected cells do not react with SV40 T antigen by immunofluorescence but do react with an antigen in the nucleus of SV40-transformed cells and with an early, cytosine arabinoside-resistant antigen present in the nucleus of SV40-infected cells. A heat-stable SV40 antigen detectable by complement fixation with T(+)U(+) hamster sera is present in extracts of SV40-induced hamster tumors and in cell packs of SV40-infected or -transformed cells. SV40 U-antigen synthesis by Ad2(+)ND(1) virus is partially sensitive to inhibitors of deoxyribonucleic acid synthesis, whereas U-antigen synthesis by SV40 virus is an early cytosine arabinoside-resistant event. As an early SV40 antigen differing from SV40 T antigen, U antigen may play a role in malignant transformation mediated by SV40.